On-Chip Micro Temperature Controllers Based on Freestanding Thermoelectric Nano Films for Low-Power Electronics - Jin, Qun; Guo, Tianxiao; Pérez, Nicolás; Yang, Nianjun; Jiang, Xin; Nielsch, Kornelius; Reith, Heiko (Nano-Micro Letters, 2024)
Multidimensional integration and multifunctional component assembly have been greatly explored in recent years to extend Moore’s Law of modern microelectronics. However, this inevitably exacerbates the inhomogeneity of temperature distribution in microsystems, making precise temperature control for electronic components extremely challenging. Herein, we report an on-chip micro temperature controller including a pair of thermoelectric legs with a total area of 50 × 50 μm2, which are fabricated from dense and flat freestanding Bi2Te3-based thermoelectric nano films deposited on a newly developed nano graphene oxide membrane substrate. Its tunable equivalent thermal resistance is controlled by electrical currents to achieve energy-efficient temperature control for low-power electronics. A large cooling temperature difference of 44.5 K at 380 K is achieved with a power consumption of only 445 μW, resulting in an ultrahigh temperature control capability over 100 K mW−1. Moreover, an ultra-fast cooling rate exceeding 2000 K s−1 and excellent reliability of up to 1 million cycles are observed. Our proposed on-chip temperature controller is expected to enable further miniaturization and multifunctional integration on a single chip for microelectronics. Highlights: 1 Dense and flat freestanding Bi2Te3-based thermoelectric nano films were successfully fabricated by sputtering technology using a newly developed nano graphene oxide membrane as a substrate. 2 On-chip micro temperature controllers were integrated using conventional micro-electromechanical system technology, to achieve energy-efficient temperature control for low-power electronics. 3 The tunable equivalent thermal resistance enables an ultrahigh temperature control capability of 100 K mW−1 and an ultra-fast cooling rate exceeding 2000 K s−1, as well as excellent reliability of up to 1 million cycles.